2013
DOI: 10.1186/1471-2474-14-182
|View full text |Cite
|
Sign up to set email alerts
|

Stability of conditioned pain modulation in two musculoskeletal pain models: investigating the influence of shoulder pain intensity and gender

Abstract: BackgroundSeveral chronic pain populations have demonstrated decreased conditioned pain modulation (CPM). However there is still a need to investigate the stability of CPM paradigms before the measure can be recommended for implementation. The purpose of the present study was to assess whether shoulder pain intensity and gender influence CPM stability within and between sessions.MethodsThis study examined two different musculoskeletal pain models, clinical shoulder pain and an experimental model of shoulder pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 55 publications
(88 reference statements)
3
73
1
1
Order By: Relevance
“…They reported sex differences for the magnitude and stability of the CPM effect; however, regarding demographic and psychological variables, there was no significant association with CPM magnitude or stability and sex. This was supported by Valencia et al 39 in an investigation of the influence of shoulder pain intensity and sex on CPM stability in patients with presurgical and postsurgical shoulder pain and in healthy volunteers with exercise-induced shoulder pain. They found while the reliability of CPM was not related to shoulder pain intensity in either group, the reliability of the CPM effect differed between sexes with female patients and male healthy volunteers demonstrating greater reliability.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…They reported sex differences for the magnitude and stability of the CPM effect; however, regarding demographic and psychological variables, there was no significant association with CPM magnitude or stability and sex. This was supported by Valencia et al 39 in an investigation of the influence of shoulder pain intensity and sex on CPM stability in patients with presurgical and postsurgical shoulder pain and in healthy volunteers with exercise-induced shoulder pain. They found while the reliability of CPM was not related to shoulder pain intensity in either group, the reliability of the CPM effect differed between sexes with female patients and male healthy volunteers demonstrating greater reliability.…”
Section: Discussionmentioning
confidence: 58%
“…Two studies, Olesen et al 32 and Valencia et al 39 investigated sequential CPM paradigms with reliability reported as poor, and good to excellent, respectively. The remainder investigated parallel paradigms with intersession reliability ranging from poor to good; therefore, it is impossible to conclude from the available evidence if there is greater reliability for one paradigm over another (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The potential contributors to pain amplification are multifactorial, therefore we hypothesize that the combined personalized intervention group will show the largest reduction in measures indicative of pain amplification. All pain sensitivity measures will be obtained by psychophysical sensory testing per established protocols established from the initial funding period [9194]. All stimuli will be delivered to bilateral upper extremities to allow for side to side comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…In order to standardize the scaling instructions, standard instructions[95] will be used for all subjects. Exact parameters for these QST measures are explained in more detail in publications from the initial funding period [9194]. These measures were selected because we expected them to be responsive to the combined personalized intervention and associated with pain relief.…”
Section: Methodsmentioning
confidence: 99%
“…The BPI is considered a valid and reliable measure of musculoskeletal pain 22,23 and has been used previously in surgical shoulder studies. 24,25 Next, patients indicated shoulder disability using the Disability of Arm, Shoulder, and Hand Quick Form Outcome Measure (QuickDASH). The QuickDASH is an 11-item patient-reported measure which rates the ability to perform personal, home, work and community tasks.…”
Section: Methodsmentioning
confidence: 99%